2022
DOI: 10.1186/s12989-022-00505-7
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylarginine dimethylaminohydrolase 1 protects PM2.5 exposure-induced lung injury in mice by repressing inflammation and oxidative stress

Abstract: Background Airborne fine particulate matter with aerodynamic diameter ≤ 2.5 μm (PM2.5) pollution is associated with the prevalence of respiratory diseases, including asthma, bronchitis and chronic obstructive pulmonary disease. In patients with those diseases, circulating asymmetric dimethylarginine (ADMA) levels are increased, which contributes to airway nitric oxide deficiency, oxidative stress and inflammation. Overexpression of dimethylarginine dimethylaminohydrolase 1 (DDAH1), an enzyme de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…DDAH1 also exerted significant protective effects against CCl 4 -induced hepatotoxicity. These results were consistent with our previous findings that DDAH1 has antioxidant effects on aged and diabetic kidneys [ 10 ], fatty livers [ 7 ], and PM 2.5 -exposed lungs [ 11 ]. As ADMA accumulation can not only inhibit NO production but can also promote ROS production by uncoupling NOS [ 12 ], it is undisputed that the antioxidant effect of DDAH1 under stress conditions is related to ADMA degradation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…DDAH1 also exerted significant protective effects against CCl 4 -induced hepatotoxicity. These results were consistent with our previous findings that DDAH1 has antioxidant effects on aged and diabetic kidneys [ 10 ], fatty livers [ 7 ], and PM 2.5 -exposed lungs [ 11 ]. As ADMA accumulation can not only inhibit NO production but can also promote ROS production by uncoupling NOS [ 12 ], it is undisputed that the antioxidant effect of DDAH1 under stress conditions is related to ADMA degradation.…”
Section: Discussionsupporting
confidence: 93%
“…Ddah1 deletion also attenuated the induction of SRXN1 and PRDX4 expression in the livers of CCl 4 -treated mice. The regulatory effects of DDAH1 on antioxidant enzymes have also been observed in PM 2.5 -exposed lungs [ 11 ] and in patients with cardiotoxin-induced muscle injury [ 9 ], acute myocardial infarction-induced heart failure [ 43 ] and diabetic nephropathy [ 10 ]. Notably, the underlying mechanism by which DDAH1 regulates antioxidant enzymes is complex and enzyme/cell/tissue dependent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous review reported that oxidative stress and inflammation was one of the hallmarks of environmental insults, and the overwhelming oxidative stress results in cell death and organ damage (Peters et al, 2021). The increased oxidative stress was a key mechanism that PM 2.5 induced damages (Gao et al, 2022; Jiang, Liang, et al, 2021; Jo et al, 2021; Li et al, 2021). The biological oxidation has initiated in the A5‐24 h group, and the stress has significantly shown in A5‐G12.…”
Section: Discussionmentioning
confidence: 99%